Innovative Nutritional Approach to Attenuate the Progression of HIV to AIDS Among People Living with HIV (PLWH): A Study Based in Abuja, Nigeria - Amlogu, Abraham Mainaji; Tewfik, Sundus; Wambebe, Charles; Tewfik, Ihab (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2019)
The success of recent nutrition interventions in HIV demonstrate the progress made in HIV care and support. The idea to adapt principles and technologies from the TFR concept to the development of a functional recipe to slow the progression of HIV to AIDS proves to be meaningful and realisable in Amtewa meal nutrition intervention approach. Although the achieved results take the form of specific technology, it suggests that a prolong consumption of the intervention meal (Amtewa) will be suitable to sustain the gained improvements in the anthropometric and biochemical indices. The research highlighted crucial issues and identified key design parameters that require further attention and research in developing countries like Nigeria. Overall, it addresses the synergistic relationship between nutrition and HIV infection, the nutritional requirement and nutritional care and support for PLWHIV in Nigeria. While the nutrition intervention demonstrated a positive effect, the study also suggests that the initial visit of a newly diagnosed HIV-positive patient should include screening for nutritional status, identify risks and offer appropriate nutrition counseling which was not in existence but currently has been imbedded as “Nutritional Framework” within the HIV care and support programme in one of the accredited HIV treatment centres in Nigeria. This Nutritional Framework has provided information to PLWHIV on their HIV medication and food interactions and about nutritional screening tools available in the health setting. Finally, the research provides evidence which may be used as a basis for policy makers to incorporate Amtewa meal nutrition intervention in HIV care and support programme in other HIV treatment centres in Nigeria with a view of attenuating the progression of HIV to AIDS amongst PLWHIV in Nigeria.